Corporate bond market reactions to quantitative easing during the COVID-19 pandemic - Nozawa, Yoshio; Qiu, Yancheng (Journal of Banking & Finance, 2021)
Using transaction data from the first half of 2020, we examine the reaction of corporate credit spreads to the Federal Reserve’s monetary policy announcements. We find evidence that the bond markets are segmented across credit ratings, which led to different initial reactions across bonds with different credit ratings but spread across various sectors of corporate bonds over the longer event window. To quantify the default risk channel of quantitative easing, we apply the variance decomposition approach to credit spreads and find that a significant fraction of credit spread changes indeed correspond to reduced default risk caused by the corporate bond purchase program. In contrast, we only find mixed evidence for the liquidity channel driving the market reaction.